PENGGUNAAN MEDIA BUKU CERITA BERGAMBAR DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS II SDN 1 SEDENG - Sintya Saputri; Afid Burhanuddin; Lina Erviana (Scholarly Journal of Elementary School, 2026)
Picture story books are able to attract attention because their appearance is very much liked by children, reading picture stories stimulates children's imagination and curiosity about an event. This study aims to determine the learning process and results of students' reading activities using picture story books in improving the early reading skills of grade II students at SDN 1 Sedeng. This study uses a qualitative research type, with a descriptive method. The subjects of the study included the homeroom teacher for grade II and 7 grade II students at SDN 1 Sedeng. Data collection techniques were carried out through observation, interviews, tests, and documentation. The results of this study in the use of picture story books in grade II of SDN 1 Sedeng effectively improved students' reading skills, especially for those who were slow readers. Interesting illustrations and simple texts make students more enthusiastic and easy to understand the contents of the story. Although there are obstacles such as excessive focus on pictures and difficulty reading long words, this media still helps increase students' interest, understanding, and participation in learning.